2011
DOI: 10.1159/000335813
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Reverses Dome Formation in Confluent Renal Tubular Cells

Abstract: Background/Aims. It has been shown that MDCK cells, a cell line derived from canine renal tubules, develop cell domes due to fluid pumped under cell monolayer and focal detachment from the adhesion surface. In vitro studies have shown that primary cilia of kidney tubular epithelial cells act as mechanosensors, increasing intracellular calcium within seconds upon changes in fluid shear stress (SS) on cell membrane. We then studied the effect of prolonged SS exposure on cell dome formation in confluent MDCK cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
2
20
0
1
Order By: Relevance
“…It was also reported that cryoprotective agents, such as DMSO and DMF, might induce dome formation [55], [66], [84]. In addition, it was shown that the dome formation could be reversed under conditions of mechanical stimulation (shear stress by apical flow) [81]. One of the recent reports provided additional evidence that the cyst formation induced by specific chemical agents is a property of cells with Type-1 phenotype [85].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was also reported that cryoprotective agents, such as DMSO and DMF, might induce dome formation [55], [66], [84]. In addition, it was shown that the dome formation could be reversed under conditions of mechanical stimulation (shear stress by apical flow) [81]. One of the recent reports provided additional evidence that the cyst formation induced by specific chemical agents is a property of cells with Type-1 phenotype [85].…”
Section: Discussionmentioning
confidence: 93%
“…The liquid-filled structures formed by MDCK cells were first described in 1969 and named “domes” [65], and the phenomenon was well investigated as a model of epithelial cell function. It was determined that dome formation is sustained by tight intercellular junctions and associated with a unidirectional ion transport into a lumen formed between a solid substratum and the basolateral cell surface, resulting in change of the osmotic pressure, followed by the flow of water into the lumen and inflation of blister-like domes [54], [55], [66], [81][84]. The published material regarding which type of cell (Type-1 or Type-2) has a tendency of dome formation is inconsistent, especially taking into account the fact that in many cases dome formation was investigated using specific chemical stimulants, hormones, or special culture medium composition affecting the salt balance [21], [24], [48], [53], [55], [57], [60], [66], [83][88].…”
Section: Discussionmentioning
confidence: 99%
“…Our simplifying assumptions minimize the specific biological details that have yet to be accounted for to perform a quantitative comparison with experimental data. In particular, tight junctions act as diffusive barriers for different classes of ions across claudin pores (20,21). For the sake of simplicity, we account for their activity as a steady factor included in the hydrodynamic resistance of the paracellular cleft.…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic stress increased the paracellular permeability of Caco-2 intestinal epithelial cells [130]. Cattaneo et al [131] attributed collapse of domes in MDCK Type II renal epithelial cell cultures exposed to shear stress to increased paracellular permeability although they did not measure paracellular permeability directly. Cavanaugh et al [99] and Cohen et al [126] concluded that the effect of stretch increased the number of large pores without significantly changing the pore radius.…”
Section: What Is the Leak Pathway?mentioning
confidence: 99%